PERILAKU DAN KUALITAS HIDUP TENTANG GIGI BERJEJAL MURID SLT 12 BANDA ACEH - Mardelita, Sisca; Keumala, Cut Ratna (Program Studi Ners UNIVERSITAS SARI MUTIARA INDONESIA, 2022)
Dental and oral health is essential for general health and well-being and greatly affects the quality of life including speech, chewing, and self-confidence. Various diseases and disorders of the teeth and mouth can affect various functions, one of which is a disorder of the arrangement of teeth or malocclusion. A malocclusion is a form of occlusion that deviates from the standard form. This study aimed to determine the relationship between adolescent behavior regarding crowding of teeth, whether only about one or more teeth. The sample used the total population technique, namely the entire population, was sampled by 55 respondents and analyzed the data with the chi-square test. The results showed that most of the respondents had unfavorable behavior about crowding teeth, as many as 65.4%. The author assumes that respondents lack information about everything related to crowding teeth, causing them not to pay attention to the condition of their teeth properly. Questionnaire data showed poor dental maintenance behavior. In the statement about the quality of life, respondents did not feel that there was anything wrong, so they should be ashamed and not confident about the condition of their teeth. They only get annoyed when their teeth hurt. It can be concluded that the dominant adolescent behavior in the poor category is 65.4%, but the quality of life is dominant in the good category as much as 50.9%. It is suggested that respondents improve good behavior about crowding teeth so that their quality of life of respondents is getting better to avoid dental and oral diseases.